Diabetes Is Associated With Rapid Progression of Aortic Stenosis: A Single-Center Retrospective Cohort Study - Han, Kangning; Shi, Dongmei; Yang, Lixia; Xie, Meng; Zhong, Rongrong; Wang, Zhijian; Gao, Fei; Ma, Xiaoteng; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2022)
Background: Mounting evidence indicates that rapid progression of aortic stenosis (AS) is significantly associated with poor prognosis. Whether diabetes accelerates the progression of AS remains controversial. Objectives: The purpose of the present study was to investigate whether diabetes was associated with rapid progression of AS. Methods: We retrospectively analyzed 276 AS patients who underwent transthoracic echocardiography at least twice with a maximum interval ≥ 180 days from January 2016 to June 2021. AS severity was defined by specific threshold values for peak aortic jet velocity (Vmax) and/or mean pressure gradient (MPG). An increase of Vmax ≥ 0.3m/s/year was defined as rapid progression. The binary Logistic regression models were used to determine the association between diabetes and rapid progression of AS. Results: At a median echocardiographic follow-up interval of 614 days, the annual increase of Vmax was 0.24±0.47 m/s. Compared with those without rapid progression, patients with rapid progression were older and more likely to have diabetes (P = 0.040 and P = 0.010, respectively). In the univariate binary Logistic regression analysis, diabetes was associated with rapid progression of AS (OR = 2.02, P = 0.011). This association remained significant in the multivariate analysis based on model 2 and model 3 (OR = 1.93, P = 0.018; OR = 1.93, P = 0.022). After propensity score-matching according to Vmax, diabetes was also associated rapid progression of AS (OR = 2.57, P = 0.045) Conclusions: Diabetes was strongly and independently associated with rapid progression of AS.